Field Dissiation Kinetics of Paraquat in Acid Soil as Function of Concentration and its Residues in Tea Leaves - Janaki, P.; Chinnusamy, C. (Asian Journal of Chemistry, 2016)
The increasing concern on ecological and public health confined the use of pesticides in agriculture. However the herbicide use is increasing alarmingly to address the issues of labour scarcity and have timely weed management in crop production. Paraquat is toxicity class I herbicide as per EPA classification and is continuously used throughout world as well as in India. Thus, to monitor residues in tea leaves, paraquat dissipation studies were conducted in acid soil under tea in tropical hilly zone. A tea grown field was applied with paraquat dichloride at 2 and 4 kg a.i. ha-1 as post-emergent herbicide. The paraquat dissipation in soil followed first-order reaction kinetics and its persistence increased with increase in the application rate. The half-life values calculated was ranged from 25.0 and 27.4 days. Detector response was linear within 0.05-1.0 μg mL-1 concentration range at per cent relative standard deviation of 3.14 %. The limit of quantification for soil and tea leaves were 0.08 and 0.05 mg kg-1, respectively. The average recoveries of paraquat from soil and tea leaves were found between 77.8-84.0 % and 82.0-84.0 %, respectively. At both the application rates, residue of paraquat was BDL in soil and tea leaves on 100 day after application.